Interpretasi Teks Dan Klaim Eksklusif Kebenaran Agama (Kontribusi Pemikiran Mohammed Arkoun Dalam Studi - Hironimus Bandur (STIPAS St. Sirilus Ruteng, 2019)
The text of the Scriptures is basically neutral but also dynamic. Scripture text can change in a dynamic line when entering the life space (context) of each owner of the text. The text makes a person more alive because of the text and context involved in the dialectics of human life both as individualy and society. Mohammed Arkoun contributed some of his critical thoughts about the interpretation of the text in dialectical conditions of text and context. Arkoun’s ideas belong to a revolutionary epistemological idea. On the one hand, Arkoun believes in God’s messages as the only source of truth, and singularly, on the other hand Arkoun sues the truth when ithas beenat human hands. For Arkoun, the text must always be adapted to the context. Text always has space and time. Therefore, the matter of claiming exclusive truth in each religion should not provoke the conflict. Arkouns’s idea could be an inspiration in improving dialogue interreligious in Indonesia.